Afforestation targets according to remote sensing techniques and geographic information systems in Imam Turki bin Abdullah Royal Natural Reserve - Al-Dughairi, Ahmed Abdullah (Journal of natural sciences, life and applied sciences, 2023)
Imam Turki bin Abdullah Royal Natural Reserve is one of the reserves surrounding Kingdom of Saudi Arabia. The reserve occupies parts of central, northern and eastern Saudi Arabia, as it is located in parts of Al-Qassim region, Ha'il region, the eastern region and the northern border region. This study is in solidarity with the vision of Green Kingdom of Saudi Arabia, which is striving tirelessly to develop and manage its natural reserves that have suffered and are suffering from environmental stress for previous long periods of time. As well, the study's targets come in line with the relentless efforts made by the Imam Turki bin Abdullah Reserve Development Authority in managing this reserve, as it exerted tremendous efforts through which it sought to re-develop the natural vegetation cover in an attempt to bringing it to its fertile past again when the environmental -balance was dominant in all its parts. The use of remote sensing techniques represented by spectral indicators of vegetation cover and ground covers, in addition to the development of visual data processing techniques, contributed to the extraction of all natural environments in the reserve. From another perspective, it also enabled the mentioned techniques to extract the land distribution of tree and shrub vegetation covers, and to identify the natural sites suitable for afforestation. It also enabled to redraw the environment of the old vegetation cover within the spatial boundaries of the reserve. The study has led to establishing future strategies in an attempt to estimate the numbers of trees and shrubs that can be cultivated in their natural environment. The results of the study led to providing a vision about estimating the current number of trees and shrubs in the reserve; which are estimated at one billion and seventy thousand. The study also contributed to eliciting a number of results that support the scheme, such as determining the depths of water in some sides of the reserve, including, Wadi As-Sahl, Al- Taisiya Reserve, as well as As-Sayd Reserve, as well as the completion of a soil database in the reserve.
Keywords: Al-Taisiya Reserve; Al-Dahna; Natural Environment; As-Sayd Reserve; Spectral Indicators; Trees; Shrubs